Art education lecturers’ intention to continue using the blackboard during and after the COVID-19 pandemic: An empirical investigation into the UTAUT and TAM model - Almogren, Abeer S. (Frontiers in Psychology, 2022)
The success of faculty in adopting technology in this digital era has a direct impact on the success of the students and, eventually, the educational institution. Many teachers, on the other hand, have yet to implement technological tools such as Canvas into their classes. As a result, this study looked at art school lecturers' opinions of variables influencing actual blackboard use, as well as their desire to utilize the lesson plan in learning and teaching during the COVID-19 Pandemic. The TAM model and the unified theory of acceptance and use of technology (UTAUT) were used to analyze lecturers' satisfaction with the blackboard and their desire to continue using it, as well as the actual usage of blackboards. A survey of 159 professors using Canvas in art instruction at five Saudi Arabian public institutions yielded the research findings. In addition, structural equation modeling (SEM) was used to evaluate the study model as well as the mediating relationship between factors influencing the desire to implement the lesson in learning and teaching during the COVID-19 Pandemic. According to the study's findings, superior impact, performance expectation, effort expectations, enabling conditions, and reported enjoyment all had statistically significant effects on perceived usefulness and perceived ease of use. The current study discovered that perceived usefulness and perception of use had statistically significant influence on behavior intent, actual blackboard usage, and lecturers' happiness with utilizing blackboard in learning and teaching during the COVID-19 Pandemic. Furthermore, the results demonstrate that lecturer's intention to continue utilizing chalkboard in learning and teaching during and after COVID-19 Pandemic was influenced by actual usage of blackboard and reported pleasure. The findings are useful for education based, regulators, and practitioners who seek to create and enhance effective methods to use e-learning systems during and after the COVID-19 Pandemic.